RELEVANSI KEIKUTSERTAAN INDONESIA DALAM INTERNATIONAL REGISTRATION OF MARKS MADRID SYSTEM MELALUI RATIFIKASI MADRID PROTOCOL TERHADAP POTENSI PENINGKATAN DAYA SAING BANGSA INDONESIA DI BIDANG PERDAGANGAN INTERNASIONAL - Irna Nurhayati; Agustina Merdekawati (Fakultas Hukum Universitas Gadjah Mada, 2008)
Protection of marks is relied on first to file principle, which means that mark protection will only be given by registration. The marks registration can be done through both national and international registration. The Madrid Protocol is an international marks registration within Madrid System, which is one of several international marks registration systems in the world. Indonesia now is still studying the benefits and detriments that would be reached if it joined in the Madrid Protocol. The research found that, first; the Madrid Protocol has both advantages and disadvantages. Second; Indonesia would gain much benefit by joining in this system. However, many things should be prepared well in order to minimize the detriment that would occur.